Evaluasi Implementasi Supervisi Keperawatan di Ruang Rawat Inap Terpadu Rumah Sakit H. Adam Malik Medan - Emilia Khairani Majid; Mappeaty Nyorong; Nuraini Nuraini (JUMANTIK (Jurnal Ilmiah Penelitian Kesehatan), 2022)
Supervision and evaluation is an important part of management to be able to manage professional nursing care, therefore as a nursing leader must have the ability to carry out supervision and evaluation. The purpose of the study was to evaluate the implementation of nursing supervision in the integrated inpatient room at H. Adam Malik Hospital, Medan. The research design used was qualitative research. The research informant was the head of the nursing field, the head of the room, the nursing committee and the implementing nurse. Interview data collection techniques, the data obtained were validated by means of triangulation of data sources. The results showed that the implementation of nursing supervision was based on planning as a reference and included in the activity agenda. There is no organizational structure yet, but it is carried out according to the duties and functions of each unit. Directions are carried out on an ongoing basis, supervision is carried out to avoid service errors to patients, evaluation of poor performance is carried out by coaching, and the recording and reporting system is running well. The conclusion of the informant that the implementation of nursing supervision in planning, organizing, guiding, directing, monitoring, evaluating, recording and reporting systems has been going well. Suggestions to the hospital can be used as a reference in the implementation of supervision and can be maintained or can be improved again.Keywords: implementation, organizing, directing, supervising nursing supervision